Inovasi Produk Ramah Lingkungan: Ember Tumpuk sebagai Solusi Pengelolaan Limbah Rumah Tangga dan Pembuatan Lilin Aromaterapi dari Minyak Jelantah: Pengabdian - Hani Humaeriyah; Hilma Marisa; Putri Rahmawati; Firda Fauziyyah; Nada Salma Salsabila; Azzahra Nur Khoiriyah; Martindo Alexander; Muthia Tsabita; Zahra Shabira Nikmati; Sofwan Adima Nurfadillah; Muhammad Hilman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The issue of household waste management remains a significant challenge in society, including in Bongkok Village, Paseh Subdistrict, Sumedang Regency. Low awareness and limited utilization of waste often lead to environmental pollution and potential health problems. Through the Community Service Program Kuliah Kerja Nyata (KKN) of Universitas Muhammadiyah Bandung, Group 27 conducted educational and training activities for the community, especially housewives, on managing used cooking oil (minyak jelantah) and organic waste by applying the 3R concept (reduce, reuse, recycle). The innovation introduced includes processing household waste into aromatherapy candles made from used cooking oil, providing economic value while being environmentally friendly. Meanwhile, organic waste is processed into compost and liquid fertilizer using the stacked bucket method (ember tumpuk). This program aims to improve the community’s knowledge, skills, and awareness of responsible waste management while offering practical solutions to reduce environmental pollution. The results show an increase in community enthusiasm and understanding of the importance of proper household waste management. It is expected that, through this activity, the community will become more independent and actively contribute to creating a cleaner, healthier, and more productive environment.